PSORIASIS IMMUNOPATHOGENESIS - Osório, Filipa (2016)
Psoriasis is a common disease, whose treatment has evolved with new discoveries on its pathogenesis. Thus it becomes important to study the involved molecular and immune mechanisms to best understand current treatment and potential therapeutic targets. In this paper we aim to review current knowledge on psoriasis pathogenesis. We describe the proposed role for the immune system, the keratinocytes and the microvasculature. The immune system is currently considered the primary pathogenic modulator and we describe T lymphocytes and other cell types role, cytokines, chemokines and counterregulatory mechanisms. Known as a genetic and environmental disorder, we refer to associated genetic polymorphisms and the relation to the expression of microRNAs.